Is an opportunistic primary care-based intervention for non-responders to bowel screening feasible and acceptable? A mixed-methods feasibility study in Scotland. Issue 10 (11th October 2017) - Calanzani, Natalia; Cavers, Debbie; Vojt, Gabriele; Orbell, Sheina; Steele, Robert J C; Brownlee, Linda; Smith, Steve; Patnick, Julietta; Weller, David; Campbell, Christine
Abstract : Objectives: We aimed to test whether a brief, opportunistic intervention in general practice was a feasible and acceptable way to engage with bowel screening non-responders. Design: This was a feasibility study testing an intervention which comprised a brief conversation during routine consultation, provision of a patient leaflet and instructions to request a replacement faecal occult blood test kit. A mixed-methods approach to evaluation was adopted. Data were collected from proformas completed after each intervention, from the Bowel Screening Centre database and from questionnaires. Semi-structured interviews were carried out. We used descriptive statistics, content and framework analysis to determine intervention feasibility and acceptability. Participants: Bowel screening non-responders (as defined by the Scottish Bowel Screening Centre) and primary care professionals working in five general practices in Lothian, Scotland. Primary and secondary outcome measures: Several predefined feasibility parameters were assessed, including numbers of patients engaging in conversation, requesting a replacement kit and returning it, and willingness of primary care professionals to deliver the intervention. Results: The intervention was offered to 258 patients in five general practices: 220 (87.0%) engaged with the intervention, 60 (23.3%) requested a new kit, 22 (8.5%) kits were completed and returned. Interviews and questionnaires suggest that the intervention was feasible, acceptable and consistent with an existing health prevention agenda. Reported challenges referred to work-related pressures, time constraints and practice priorities. Conclusions: This intervention was acceptable and resulted in a modest increase in non-responders participating in bowel screening, although outlined challenges may affect sustained implementation. The strategy is also aligned with the increasing role of primary care in promoting bowel screening.